The Implementation of Pre Merger Notification in The Draft Law on The Prohibition of Monopoly Practices and Unhealthy Business Competition in Indonesia - Sumirat, Ratna; Dirkareshza, Rianda (Faculty of Law, Universitas Brawijaya, 2021)
This paper examines the consequences of the Post Merger regime in Law No. 5/1999 concerning the Prohibition of Monopolistic Practices and Business Competition. This research uses the normative juridical method and comparative approach, comparing the American Antitrust Law which has successfully implemented the pre merger notification with the Indonesian Business Competition Law which implements the post merger notification. The results of this study indicate that the importance of implementing the Pre Merger Notification in the draft Law on the Prohibition of Monopolistic Practices and Unfair Business Competition is viewed in a comparison with the success of the Antitrust Law America and supported by the dynamics of globalization of the Industrial Revolution 4.0 which became a challenge for the Business Association Supervisory Commission. Thus, the regime change from Post Merger Notification to Pre Merger Notification is the right step in implementing a merger in Indonesia because Pre Merger Notification provides legal certainty and also more efficient for business actors and KPPU as a preventive effort with the aim that the implementation of Pre Merger Notification will be carried out optimally in achieving the goal of fair business competition.